A potential link between fibroblast growth factor-23 and the progression of AKI to CKD - Yinghui Lu; Shutian Xu; Rong Tang; Cui Han; Chunxia Zheng (BMC Nephrology, 2023)
Abstract Background Patients who recover from acute kidney injury (AKI) have a 25% increase in the risk of chronic kidney disease (CKD) and a 50% increase in mortality after a follow-up of approximately 10 years. Circulating FGF-23 increases significantly early in the development of AKI, is significantly elevated in patients with CKD and has become a major biomarker of poor clinical prognosis in CKD. However, the potential link between fibroblast growth factor-23 levels and the progression of AKI to CKD remains unclear. Method Serum FGF-23 levels in AKI patients and ischaemia‒reperfusion injury (IRI) mice were detected with ELISA. Cultured HK2 cells were incubated with FGF-23 and PD173074, a blocker of FGFR, and then TGFβ/Smad and Wnt/β-catenin were examined with immunofluorescence and immunoblotting. Quantitative real-time polymerase chain reaction was used to detect the expression of COL1A1 and COL4A1. Histologic staining confirmed renal fibrosis. Results The level of serum FGF-23 was significantly different between AKI patients and healthy controls (P < 0.01). Moreover, serum FGF-23 levels in the CKD progression group were significantly higher than those in the non-CKD progression group of AKI patients (P < 0.01). In the AKI-CKD mouse model, serum FGF-23 levels were increased, and renal fibrosis occurred; moreover, the protein expression of β-catenin and p-Smad3 was upregulated. PD173074 downregulated the expression of β-catenin and p-Smad3 and reduced fibrosis in both mice and HK2 cells. Conclusion The increase in FGF-23 may be associated with the progression of AKI to CKD and may mediate renal fibrosis via TGF-β and Wnt/β-catenin activation.